ATRT-27. A PHASE II STUDY OF PANOBINOSTAT IN PAEDIATRIC PATIENTS WITH SOLID TUMORS INCLUDING MALIGNANT RHABDOID TUMOR/ATYPICAL TERATOID RHABDOID TUMOURS. Issue 2 (22nd June 2018) - Wood, Paul; Desai, Jayesh; Gottardo, Nick; Cain, Jason; Ashley, David
Abstract: BACKGROUND: Low-dose panobinostat treatment has been shown to terminally differentiate malignant rhabdoid tumor (MRT)/atypical teratoid rhabdoid tumors (ATRT) in pre-clinical models. OBJECTIVES: This will be an open label, phase II study, of panobinostat in patients with newly diagnosed MRT/ATRT, aimed to define the anti-tumour activity of panobinostat. PRIMARY AIMS: To define the anti-tumour activity of low dose continuous panobinostat. To define and describe the associated toxicities of panobinostat. SECONDARY AIMS: To define the anti-tumor activity of low dose, continuous panobinostat using functional imaging techniques. To assess the biologic activity of low dose panobinostat by measuring histone acetylation status in peripheral mononuclear cells (PMNC) and markers of differentiation in fresh tumour tissue specimens in all patients (when available). STUDY DESIGN: Pediatric patients with newly diagnosed MRT/ATRT will be eligible to be enrolled. Following initial cycles of chemotherapy and/or radiation treatment panobinostat will be administered as a continuous daily oral dose starting at 10mg/m 2 . There will be a three-week wash out period between therapies. Real-time acetylation status, using acetylated H3 & H4 on PMNC, will determine biological activity of panobinostat in the first two patients enrolled. A second analysis will be performed after nine patients have been enrolled. The regimen will be considered worthy of further study if disease stability of more than three of the first nine patients, with less than 30% of patients experiencing grade 3 and/ or 4 adverse events, at four months. If this is achieved the study will proceed to recruit a total of 20 patients.